Cumulative IgE-levels specific for respiratory allergens as biomarker to predict efficacy of anti-IgE-based treatment of severe asthma - Naumova, Veronika; Beltyukov, Evgeny; Niespodziana, Katarzyna; Errhalt, Peter; Valenta, Rudolf; Karaulov, Alexander; Kiseleva, Darina (Frontiers in Immunology, 2022)
Molecular therapies, including anti-IgE, biologicals and small molecules are increasingly used for treatment of asthma. The effectiveness of these therapies may be increased with biomarkers. Aim of this study was to assess the value of measuring cumulative IgE levels specific for respiratory allergens to increase the efficacy of anti-IgE therapy for severe bronchial asthma. One hundred and thirty seven patients with severe asthma were recruited from 2016 to 2022. Standard empirical allergy diagnosis (i.e., anamnesis, skin testing, allergen-specific IgE measurement), blood eosinophil counting, measurement of total IgE and of cumulative IgE-specific for respiratory allergens by Phadiatop™ were performed. Thirty four patients with severe allergic asthma, for whom all three diagnostic methods were performed, were then used to analyze the efficacy of anti-IgE treatment in patients stratified in two groups according cumulative IgE levels specific for respiratory allergens determined by PhadiatopTM. Group #1 patients (n = 8) had cumulative specific IgE values ≥ 0.35 and < 1.53 PAU/l while in group #2 patients (n = 26) they were ≥ 1.53 PAU/l. Treatment with Omalizumab was performed for at least 12 months. The level of asthma control (ACT questionnaire), the number of asthma exacerbations, the quality of life (AQLQ questionnaire), the need for systemic corticosteroids, and the respiratory function (FEV1) was determined by “before-after” analysis for each group, followed by a comparison of the dynamics between groups. In group 2 patients with an initial allergen-specific IgE level ≥ 1.53 kUA/L, the efficacy of Omalizumab treatment was significantly better regarding asthma control, number of exacerbations, and quality of life than in group 1 patients. Our study provides evidence that measuring cumulative levels of IgE specific for respiratory allergens could be a useful screening method for detecting an allergic phenotype of severe asthma and may serve as biomarker to enhance the success of IgE-targeted therapy.